جمالية النسق التعبدي في الكون، أو موسيقى الكائنات من منظور النورسي: دراسة في الكليات - إدريس التركاوي (International Institute of Islamic Thought, 2017)
للكائنات في تأملات النورسي وظيفة موسيقية جمالية في الكون، تتشكَّل من حركاتها المادية وتسبيحاتها الروحية، في دلالة ازدواجية مركبة تأبى التفكُّك؛ ما يستفز التدبر في الإنسان، ويدفعه إلى إعادة قراءة الكون والكائنات؛ قراءة تراعى فيها الوحدة الكونية والقانون التعبدي المشترك الجامع بين طبيعة الشيء المادية ووظيفته التوحيدية المعنوية، وليس الاكتفاء بإحداهما. Nursi's reflections show that creatures have an aesthetic musical function which is composed of their physical movement and spiritual glorification, which comes in inseparable compound duality. This function provokes human contemplation that requires rereading the natural cosmos and creatures in such a way that takes into account the cosmos unity and the common worship law which bring together both the physical nature of things and their moral monotheistic function.